The Differences in Student Achievement Based on Missouri Approved Teacher Evaluation Models Used - Adams, Teresa M. (Southwest Baptist University, 2020)
In response to legislation from the federal government to consider student achievement when evaluating teachers, states have created new evaluation tools. The challenge is in isolating the many variables, including the actions of the teacher, that may impact student achievement. The purpose of the causal-comparative study was to determine the difference in the percent of students scoring proficient and advanced on the Missouri Assessment Program (MAP) in third, fourth, and fifth grades, depending on which evaluation model was used to evaluate teachers between the years 2017 and 2019. In response to No Child Left Behind, the Missouri Department of Elementary and Secondary Education (MODESE) required school districts to use the DESE created Model Educator Evaluation System (MEES), or use an evaluation system based on the same principles used to create the MEES and approved by DESE. This study compared the mean MAP scores of students in third, fourth, and fifth grades in 2017, 2018, and 2019 whose teachers were evaluated using either the MEES, the Network for Educator Effectiveness (NEE), or a district created evaluation, to determine the differences in the mean scores. School districts who used the same evaluation for each of the three years were selected for the study and their total percent of proficient and advanced scores were obtained from MODESE’s open-access website. A one-way ANOVA was used to compare the means. The findings of the study showed statistically significant differences in 2017 fourth grade ELA, 2017 fourth grade math, 2017 fifth grade ELA, 2017 fifth grade math, and 2018 fourth grade ELA. While there were statistically significant difference, the effect size was low. The outcomes of the study did show the MEES had the lowest mean percent of proficient and advanced scores in all but two of the eighteen comparisons, indicating the need for additional research studies regarding the impact of teacher evaluation on student achievement.